Expanding Understanding of Community Health Worker Programs: A Cross-Sectional Survey on the Work, Satisfaction, and Livelihoods of CHWs in Madagascar. (September 2018) - Brunie, Aurélie; Mercer, Sarah; Chen, Mario; Andrianantoandro, Tokinirina
With health worker shortages in rural areas, community health workers (CHWs) are instrumental to the sustainability of primary health care and to the ability to meet health needs. Identifying appropriate operational models and incentive structures is an important element of long-term success. This article reports on CHWs' work demands and affective response to their volunteer work within the broader context of their livelihoods in Madagascar. A cross-sectional survey of 874 CHWs, called Agents de Santé Communautaire (ACs), from 14 districts across 5 regions was conducted in June 2015. Only 44% of ACs had cash savings. Subsistence farming was the main livelihood strategy; ninety-two percent of ACs were food insecure and 89% had experienced a shock in the past year. Overall, 77% of ACs financed commodity resupply through sales of health products and 18% from their personal savings; stock-outs at point of supply and financial and time constraints were the main reported challenges in getting health products. The average satisfaction score with AC work was 3 out of 4. This assessment from Madagascar helps unveil a more comprehensive view of the reality of CHWs' lives. Managers need to take into account the potential implications of the demands of CHW work on already precarious livelihoods.